2003
DOI: 10.1016/s1044-0305(03)00578-6
|View full text |Cite
|
Sign up to set email alerts
|

Fraying and electron autodetachment dynamics of trapped gas phase oligonucleotides

Abstract: Sensitive methods recently developed to measure laser-induced fluorescence from trapped ions have been applied to study the dynamics of double-and single-stranded oligonucleotides. In this paper, the fraying of duplex terminal base pairs has been identified by measuring the donor fluorescence as a function of temperature from an oligonucleotide duplex labeled with a pair of FRET dyes. Comparison of the degree of dissociation of 14-mer duplexes observed in the mass spectra with the fluorescence intensity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
47
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 32 publications
4
47
0
Order By: Relevance
“…Apart from the sequencing applications of EPD, numerous questions remain about the electron photodetachment mechanism, and how it compares with electron detachment dissociation [3][4][5] and thermal electron detachment [10,11]. We will briefly summarize our current understanding of the photodetachment mechanism [8].…”
mentioning
confidence: 99%
“…Apart from the sequencing applications of EPD, numerous questions remain about the electron photodetachment mechanism, and how it compares with electron detachment dissociation [3][4][5] and thermal electron detachment [10,11]. We will briefly summarize our current understanding of the photodetachment mechanism [8].…”
mentioning
confidence: 99%
“…Although both bare P 3 O 9 3− and Co(NO 2 ) 6 3− have been reported previously, 44 these ions are not formed under identical conditions for successfully generating Fe(CN) 6 3− (H 2 O) n . We find that P 3 O 9 3− is only observed with six or more water molecules attached, and this ion undergoes charge separation to form HP 3 O 9 2− (H 2 O) 5 + OH − . This is the first report of a critical cluster size for small trianions, and these are the smallest trianions (highest charge density) that have been observed in the gas phase.…”
Section: ■ Introductionmentioning
confidence: 75%
“…A few observations about the rates of charge loss illustrated in Figures 1 and 2 are in order: (1) The rates for -4 to -3 charge loss are higher than those for -3 to -2 charge loss; in general, it is found that rates for -n to -(n -1) charge loss are higher than those for -(n -1) to -(n -2) charge loss. (2) The activation energies for a given -n to -(n -1) charge loss vary little as the base composition of the oligonucleotide changes, but the preexponential A factors vary by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 92%